THE SOCIAL NETWORK OF HOUSEHOLD INDUSTRY FOR KAREH-KAREH CAKES IN NAGARI KOTO LAWEH, X KOTO DISTRICT - Marnelly, Tengku Romi; Forseta, Olivia; Risdayati, Risdayati; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This study describes the social networks in the household industry of Kareh-Kareh cakes in Nagari Koto Laweh, X Koto District. The aim is to investigate the form of the social network in the Kareh-Kareh household industry and how it functions in developing its business. The research used a descriptive qualitative method with ten informants, including six supporting informants, selected using purposive sampling. Data collection techniques involved observation, interviews, and documentation, while the social network concept of Granovetter was used as the theoretical framework. The research results indicate that entrepreneurs in the Kareh-Kareh cake home industry have a micro-social network that includes fellow entrepreneurs, sellers of raw materials, cake artisans, and customers, as well as meso networks with business actors such as the government, the Kharisma and Meekar capital groups, and other parties like universities and social media promotions. Norms, network density, and trust are maintained between actors to create a strong network. The function of the social network in the Kareh-Kareh cake home industry is as a lubricant, adhesive, and bridge.